AN ANALYSIS OF SUBTITLE STRATEGIES IN TRANSLATING SPEECH ACTS IN THE "UP" FILM - Eva Fauziyyah, - (2012)
The study is entitled "An Analysis of Subtitle Strategies in Translating Speech Acts in the Up Film". The purpose of this study is to examine the occurrence of speech acts and explore the subtitle strategies employed to translate the speech acts in the Up film. A descriptive qualitative research method is used to provide appropriate directions in properly collecting and analyzing the data (Fraenkel and Wallen, 1993). The study reveals that there are 770 sentences to be analyzed. As a result, the writer finds that there are 5 types of speech acts. In details, the types, their quantities and percentages are reported as follows; representative with 485 items (62.99%), directive with 196 items (25.45%), commissive with 33 items (4.29%), expressive with 53 items (6.88%), and declarative with 3 items (0.39%). Meanwhile, subtitle strategies are applied to those types of speech acts in order to obtain an appropriate subtitle. Based on the theory of Gottlieb's subtitle strategies, the film subtitle of "Up" has been analyzed and classified into 10 strategies. The most frequent strategy is transfer, which is used to translate 234 items or covers 30.39% of the whole quantity. The other subtitle strategies are paraphrase with 168 items (21.82%), deletion 128 items (16.62%), condensation with 116 items (15.1%), decimation with 67 items (8.70%), imitation with 24 items (3.12%), expansion with 23 items (2.99%), dislocation with 5 items (0.65%), transcription with 3 items (0.39%), and resignation with only 2 items (0.26%). The dominant phenomenon shows that linguistic and cultural aspects influence the result of subtitling process. It is because most of the utterances are short and can be translated easily if the translator chose the applicable subtitle strategies.